DETERMINATION OF THE POSSIBILITY OF USING A DEEP EUTECTIC SOLVENT BASED ON GLYCEROL AND CHOLINE CHLORIDE AS A PLASTICIZER FOR POLYLACTIC ACID - MYRONYUK, OLEKSIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the possibility of using a deep eutectic solvent (DES) based on glycerol and choline chloride as a potential plasticizer for polylactic acid (PLA) — a biodegradable polymer that is actively being introduced into production as a substitute for traditional petrochemical materials. Despite several advantages, PLA is characterized by a high glass transition temperature ( 60 °C), which results in its brittleness. One way to lower this temperature is by introducing plasticizers. Given the need to create more environmentally friendly systems, the authors investigate the compatibility of PLA with DES based on glycerol and choline chloride, as well as with their mixtures with polyethylene glycol (PEG 400). The first stage of the study involved calculating thermodynamic compatibility parameters according to Hansen’s theory. Using solubility parameters for PLA, PEG 400, glycerol, and choline chloride, it was found that the distance between the solubility centers of PLA and the DES (without a co-plasticizer) exceeds the radius of the polymer’s solubility sphere. The calculations showed that the introduction of at least 87.5 wt.% PEG into the system is a necessary condition to ensure thermodynamic compatibility. Subsequent experimental research involved measuring the transparency temperature of PLA powders, which allowed for the evaluation of how different plasticizer compositions affect the segmental mobility of the polymer. The obtained results demonstrated that even at a molar ratio of choline chloride to PEG of 1:1 — which formally does not meet the compatibility conditions according to the Hansen model — a significant decrease in transparency temperature (by 36 °C) was observed, indicating effective plasticization of PLA. Thus, it was shown that DES based on choline chloride and glycerol can be used as a plasticizer for PLA provided that a co-plasticizer, particularly PEG 400, is added. Furthermore, it was established that the actual effectiveness of the mixture exceeds the theoretically predicted one, opening up prospects for further research. The study also identifies possible directions for optimization, including the use of less polar DESs (e.g., based on menthol and decanoic acid), and a deeper investigation into the reasons for discrepancies between theoretical predictions and experimental results based on changes in PLA transparency temperature. The research findings may be used in the development of new environmentally friendly PLA-based compositions for packaging materials, fibers, and biomedical products.